Pengembangan Program Pencegahan Kekerasan Seksual Terhadap Anak Berkebutuhan Khusus di Dinas Pemberdayaan Perlindungan Anak dan Pengendalian Penduduk (DPPAPP) DKI Jakarta - Sonya Mutiara Sarah Runtu; Toni Yudha Pratama; Dedi Mulia; Yuni Tanjung Utami (Pusat Riset dan Inovasi Nasional, 2024)
This study focuses on the problem of sexual violence against children with special needs in DKI Jakarta, which has reached a substantial magnitude. Presently, there is a lack of a specialized preventative program that is specifically designed to address the distinct characteristics and requirements of these children. The main aim of this research is to create a program that focuses on preventing sexual violence and is tailored to meet the unique needs and circumstances of children with special needs. The chosen research approach is Research and Development (R&D), which utilizes the 4-D (Four D) development paradigm. The researchers engage in a series of developmental stages, which include the defining stage, design stage, development stage, and dissemination stage. Data were gathered using interview methodologies, then examined, and the final outcomes were authenticated by specialists. The study's findings suggest that the sexual violence prevention program designed for children with exceptional needs passed rigorous validation. The material validation score attained a percentage of 96.6, while the media validation score reached a percentage of 82.2. Furthermore, the practicality assessment of the designed program produced favorable outcomes, with a feasibility rate of 82%.